2007
DOI: 10.1051/0004-6361:20065997
|View full text |Cite
|
Sign up to set email alerts
|

Fast kink modes of longitudinally stratified coronal loops

Abstract: Aims. We investigate the standing kink modes of a cylindrical model of coronal loops. The density is stratified along the loop axis and changes discontinuously at the surface of the cylinder. The periods and mode profiles are studies with their deviation from those of the unstratified loops. The aim is to extract information on the density scale heights prevailing in the solar corona. Methods. The problem is reduced to solving a single second-order partial differential equation for δB z (r, z), the longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 30 publications
7
35
0
Order By: Relevance
“…For typical loop lengths, 100 − 400Mm, the density scale heights fall in the range of 13 − 108Mm. These results are in agreement with Verwichte et al (2004), McEwan et al (2006), and Safari et al (2007). The application of variational method in real model of coronal loop are implementing in our group.…”
Section: Resultssupporting
confidence: 85%
“…For typical loop lengths, 100 − 400Mm, the density scale heights fall in the range of 13 − 108Mm. These results are in agreement with Verwichte et al (2004), McEwan et al (2006), and Safari et al (2007). The application of variational method in real model of coronal loop are implementing in our group.…”
Section: Resultssupporting
confidence: 85%
“…It was strongly emphasised by and Verth et al (2007) that the longitudinal spatial resolution could possibly allow for the estimation of loop model parameters based on the deviations in the eigenfunctions rather than the eigenfrequencies. The effect of longitudinal density stratification on the transversal displacement amplitude was however found to be not particularly strong for the fundamental oscillation Safari et al 2007), and due to several uncertainties in the observations (projection effects, localisation of the loop footpoints), probably not detectable at present with reasonable confidence. For the first overtone however it was found that the shift of the antinodes towards the footpoints is much more pronounced and could possibly be detectable.…”
Section: Introductionmentioning
confidence: 79%
“…The derivation starts from a tube of arbitrary thickness but eventually specializes to a "thin tube" to obtain concise formulae. A similar formula (for the displacement only) was derived by Safari et al (2007) starting directly from the "thin tube" formula by Dymova & Ruderman (2005). They used it to validate the results about the modifications to the displacement profiles of the fundamental and its first harmonic by and Verth et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…They found that stratification changed the amplitude profile from one of constant longitudinal density, but that the effect was too subtle for such observational signatures to be detectable by EUV imagers. Safari et al (2007) also considered standing kink modes of longitudinally stratified coronal loops. They found changes in amplitude profiles of a few percent, consistent with Erdélyi & Verth (2007), and showed that the predicted departure of P 1 /2P 2 from unity was in good agreement with the observational data of Verwichte et al (2004).…”
Section: Introductionmentioning
confidence: 99%